2014
DOI: 10.1038/mp.2014.32
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the nucleus basalis of Meynert in Alzheimer’s dementia

Abstract: Cholinergic neurons of the medial forebrain are considered important contributors to brain plasticity and neuromodulation. A reduction of cholinergic innervation can lead to pathophysiological changes of neurotransmission and is observed in Alzheimer's disease. Here we report on six patients with mild to moderate Alzheimer's disease (AD) treated with bilateral low-frequency deep brain stimulation (DBS) of the nucleus basalis of Meynert (NBM). During a four-week double-blind sham-controlled phase and a subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(228 citation statements)
references
References 34 publications
6
209
1
5
Order By: Relevance
“…Deep brain stimulation (DBS) is a surgical technique that involves the delivery of electrical current to the brain parenchyma through implanted electrodes. In psychiatry, DBS has been approved for treatment-resistant obsessivecompulsive disorders (Hamani et al, 2014b) and is currently being investigated for depression (Holtzheimer et al, 2012;Lozano et al, 2008;Malone et al, 2009;Mayberg et al, 2005), anorexia (Lipsman et al, 2013), Alzheimer's disease (Kuhn et al, 2015;Laxton et al, 2010) and drug addiction Stelten et al, 2008;Voges et al, 2013). So far, though different targets have been proposed (Ewing and Winter, 2013;Mikell et al, 2009), no clinical trials have been reported on the use of DBS in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) is a surgical technique that involves the delivery of electrical current to the brain parenchyma through implanted electrodes. In psychiatry, DBS has been approved for treatment-resistant obsessivecompulsive disorders (Hamani et al, 2014b) and is currently being investigated for depression (Holtzheimer et al, 2012;Lozano et al, 2008;Malone et al, 2009;Mayberg et al, 2005), anorexia (Lipsman et al, 2013), Alzheimer's disease (Kuhn et al, 2015;Laxton et al, 2010) and drug addiction Stelten et al, 2008;Voges et al, 2013). So far, though different targets have been proposed (Ewing and Winter, 2013;Mikell et al, 2009), no clinical trials have been reported on the use of DBS in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…With NBM DBS off, the patient returned to his baseline poor cognitive state; with the NBM DBS on, the patient regained his cognitive improvement as before. These promising results led these authors to initiate a phase I trial of NBM DBS in six patients with mild to moderate AD, which has recently been completed and published (Kuhn et al 2015).…”
Section: Electrical Neural Stimulation For Alzheimer's Diseasementioning
confidence: 96%
“…Stimulation of the nucleus basalis of Meynert (NBM) has been used in PD dementia reported in a single case [90] and there is also a phase I trial of NBM stimulation in Alzheimer's dementia [91]. Despite the mostly advanced age of these patients, a recent analysis has shown that clinical and economic thresholds required for DBS to be cost-effective for dementia are relatively low [92].…”
Section: Lewy Body Dementiasmentioning
confidence: 98%